2007
DOI: 10.3168/jds.s0022-0302(07)71567-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat and High-Pressure Treatments on Microbiological Quality and Immunoglobulin G Stability of Caprine Colostrum

Abstract: Caprine colostrums (6 batches) were subjected to heat (56 degrees C for 60 min and 63 degrees C for 30 min) and high-pressure (400 and 500 MPa for 10 min at 20 degrees C) treatments at laboratory scale, and analyses of the main microbial groups and the extent of IgG denaturation (determined by immunodiffusion) were performed. Overall mean microbial values in raw colostrums were: total count, 5.55 log cfu/mL; Enterobacteriaceae, 2.64 log cfu/mL; lactococci, 5.41 log cfu/mL; lactobacilli, 2.34 log cfu/mL; and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 28 publications
7
46
2
Order By: Relevance
“…Conventional immunochemical techniques are particularly useful for detecting conformational changes in proteins with concomitant loss of epitopes as a result of denaturation [25]. This technique has been widely employed to study the denaturation of whey proteins subjected to technological treatments such as heat treatment [23], high-intensity pulse electric fields processing [26], or high-pressure treatment [27]. High correlation coefficients (r 2 [ 0.98) were obtained when representing the square of the diameter of precipitating rings corresponding to protein standards versus their concentration, being the relationship linear within the range from 10 to 250 lg/mL for both proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional immunochemical techniques are particularly useful for detecting conformational changes in proteins with concomitant loss of epitopes as a result of denaturation [25]. This technique has been widely employed to study the denaturation of whey proteins subjected to technological treatments such as heat treatment [23], high-intensity pulse electric fields processing [26], or high-pressure treatment [27]. High correlation coefficients (r 2 [ 0.98) were obtained when representing the square of the diameter of precipitating rings corresponding to protein standards versus their concentration, being the relationship linear within the range from 10 to 250 lg/mL for both proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of Ig stability have also revealed speciesspecific differences in the heat sensitivity of bovine, caprine and ovine IgG (Law, 1995;Trujillo et al, 2007) and between bovine IgG, IgA and IgM isotypes (Mainer et al, 1997). However, few studies have considered differentiation of Fab and Fc domains within bovine lacteal IgG with respect to relative conformational stability, and the potential for other milk components to moderate this stability, and conclusions remain equivocal (Cao et al, 2007;Dominguez et al, 1997Dominguez et al, , 2001Li et al, 2005;Ohnuki & Otani, 2005).…”
Section: Introductionmentioning
confidence: 88%
“…Each room had central heating (20°C) and 0.3 m 2 floor space per lamb. Lambs were bottle-fed a sheep colostrum pool that was previously pasteurized at 63°C for 30 min according to Trujillo et al (2007). Artificially reared lambs received colostrum amount equivalent to 4 g of IgG/kg of BW at birth (C4 group) or 8 g of IgG/kg of BW at birth (C8 group) divided into three meals at 2, 14 and 24 h after birth.…”
Section: Methodsmentioning
confidence: 99%